The longitudinal impact of reinforcement sensitivity on internet addiction among college students: the mediating role of self-control - Xue, Jinfeng; Li, Ziyi; Zhang, Wei; Li, Wendi; Liu, Li; Zhang, Zhiyou (Frontiers in Psychiatry, 2024)
Introduction As the rapid expanding of internet technology, it is necessary to pay attention to the factors that predict Internet addiction. This study aimed to investigate the longitudinal impact of reinforcement sensitivity on internet addiction among college students and the mediating role of self-control. Methods The study involves two follow-up assessments with a 5-month interval. 383 college students’ reinforcement sensitivity, self-control, and internet addiction were measured at two-time points. Results ①The revised Behavioral Approach System (r-BAS) at Time Point 1 (T1) could predict both T1 and Time Point 2 (T2) internet addiction through the complete mediation of T1 self-control. ②The revised Behavioral Inhibition System (r-BIS) at T1, along with the Fight/Flight/Freeze System (FFFS), can predict T1 and T2 internet addiction through the partial mediation of T1 self-control. Conclusion Reinforcement sensitivity can predict current and future internet addiction, with self-control playing a mediating role. This study provides longitudinal experimental evidence for the revised Reinforcement Sensitivity Theory (r-RST), further revealing the underlying mechanisms through which reinforcement sensitivity influences internet addiction. Additionally, it has implications for clinical intervention.